The instructional design of the Virtual Telemedicine: A simulation-based serious game in health care - Nicolaidou, Iolie; Antoniades, Athos; Marangos, Charis; Dafli, Eleni; Kyriacou, Efthyvoulos C.; Bamidis, Panagiotis; Pattichis, Constantinos S. (My University, 2012)
This paper is a work-in-progress report on the instructional design of Virtual Telemedicine, a simulation-based serious game in health-care. The problem that this game addresses is the need to train practicing doctors and medical students for problem-solving in real-life scenarios through a telemedicine system. In medical emergency situations a doctor is asked to make important decisions for the treatment of a patient within minutes or even seconds. His actions result in saving or losing a patient’s life. The importance of the development of this game lies on the opportunities it provides to students for practicing their patient-treatment skills in a safe and controlled e-learning environment that simulates real-life conditions but avoids the risks associated with dealing with real patients. The game makes use of data from an electrocardiogram (ECG) and its overall learning goal is for practicing doctors or medical students to learn how to respond to a medical emergency situation to treat the symptoms of a virtual patient by taking specific actions and examining their results based on immediate feedback provided by both the system and the virtual patient. Three scenarios are currently developed in the game: a) Precordial pain, in which the patient faces an acute coronary syndrome, b) Palpitations, in which the patient experiences cardiac arrhythmias and c) Syncope, in which the patient is diagnosed with an atrioventricular block. The paper reports on the instructional design objectives of the game, describes the prototype scenario and outlines the changes made as part of the game’s redesign and development to increase its pedagogical value. Some of the changes that were made to the beta-version of the game included the addition of the overall goal of the game, the objectives and context for each scenario, the patient’s history, as well as specific instructions to scaffold the user in making a choice among several treatment options. Moreover, instant feedback is now provided to the user as he receives a clearly visible positive or negative score for every one of his actions. In addition, the user can track his score while playing the game. Finally, a detailed report is provided at the end of the game outlining the user’s choices, clearly indicating which of them were successful and including the total amount of time he required to solve the problem and save the patient. The paper concludes with the description of the evaluation methodology of the Virtual Telemedicine game.
Keywords: Instructional Design; Serious Games; Simulations; Medical Education; E-Learning; Virtual Patients; Problem-Solving